2020
DOI: 10.1002/jcp.29871
|View full text |Cite
|
Sign up to set email alerts
|

LINC01426 contributes to clear cell renal cell carcinoma progression by modulating CTBP1/miR‐423‐5p/FOXM1 axis via interacting with IGF2BP1

Abstract: Increasing evidence suggests that long noncoding RNAs (lncRNAs) are pivotal regulators in oncogenesis. However, the role of numerous lncRNAs has never been unmasked in clear cell renal cell carcinoma (ccRCC). Presently, we investigated the function of long intergenic nonprotein coding RNA 1426 (LINC01426) in ccRCC, as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…The expression and function of LINC01426 in human cancers have recently attracted considerable interest. LINC01426 is upregulated in glioma, 25 clear cell renal cell carcinoma, 27 and lung adenocarcinoma, 28 and elevated LINC01426 expression is associated with adverse clinicopathological characteristics. 25,27,28 In addition, LINC01426 is reportedly an independent predictor of prognosis in glioma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression and function of LINC01426 in human cancers have recently attracted considerable interest. LINC01426 is upregulated in glioma, 25 clear cell renal cell carcinoma, 27 and lung adenocarcinoma, 28 and elevated LINC01426 expression is associated with adverse clinicopathological characteristics. 25,27,28 In addition, LINC01426 is reportedly an independent predictor of prognosis in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01426 is upregulated in glioma, 25 clear cell renal cell carcinoma, 27 and lung adenocarcinoma, 28 and elevated LINC01426 expression is associated with adverse clinicopathological characteristics. 25,27,28 In addition, LINC01426 is reportedly an independent predictor of prognosis in glioma. 25 Functionally, LINC01426 exerts pro-oncogenic activities in glioma, 25,26 clear cell renal cell carcinoma, 27 and lung adenocarcinoma, 28 and it is implicated in the regulation of multiple tumor biological phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTBP1 and HDAC2 can also inhibit miR-423-5p expression, while downregulated miR-423-5p can Targeted upregulation of FOXM1 expression to promote the progress of ccRCC. 88 In the above studies, it was found that the expression of miR-423 was often inhibited and played an anti-tumor role ( Figure 5).…”
Section: Mechanism Of Mir-423 and Lncrna In Human Tumormentioning
confidence: 91%
“…87 LINC01426 is upregulated in the renal clear cell carcinoma (ccRCC) cell line, promoting the proliferation and migration of rccRCC cells. 88 Mechanistically, LINC01426 upregulates FOXM1 expression by inhibiting miR-423-5p, while LINC01426 can recruit IGF2BP1 to increase CTBP1 expression. CTBP1 and HDAC2 can also inhibit miR-423-5p expression, while downregulated miR-423-5p can Targeted upregulation of FOXM1 expression to promote the progress of ccRCC.…”
Section: Mechanism Of Mir-423 and Lncrna In Human Tumormentioning
confidence: 99%